Contrasting calcium localization and speciation in leaves of the Medicago truncatula mutant cod5 analyzed via synchrotron X–ray techniques. (10th October 2013) - Punshon, Tracy; Tappero, Ryan; Ricachenevsky, Felipe K.; Hirschi, Kendal; Nakata, Paul A.
Summary: Oxalate‐producing plants accumulate calcium oxalate crystals (CaOx(c) ) in the range of 3–80% w/w of their dry weight, reducing calcium (Ca) bioavailability. The calcium oxalate deficient 5 ( cod5 ) mutant of Medicago truncatula has been previously shown to contain similar Ca concentrations to wild‐type (WT) plants, but lower oxalate and CaOx(c) concentrations. We imaged the Ca distribution in WT and cod5 leaflets via synchrotron X–ray fluorescence mapping (SXRF). We observed a difference in the Ca distribution between cod5 and WT leaflets, manifested as an abundance of Ca in the interveinal areas and a lack of Ca along the secondary veins in cod5, i.e. the opposite of what is observed in WT. X–ray microdiffraction (μXRD) of M. truncatula leaves confirmed that crystalline CaOx(c) (whewellite; CaC2 O4 ·H2 O) was present in the WT only, in cells sheathing the secondary veins. Together with μXRD, microbeam Ca K–edge X–ray absorption near‐edge structure spectroscopy (μXANES) indicated that, among the forms of CaOx, i.e. crystalline or amorphous, only amorphous CaOx was present in cod5 . These results demonstrate that deletion of COD5 changes both Ca localization and the form of CaOx within leaflets.